Meistera caudata and Meistera sudae (Zingiberaceae: Alpinieae), two new ginger species from Bidoup-Núi Bà National Park, southern Vietnam - Šída, Otakar; Kuznetsov, Andrey; Kuznetsova, Svetlana; Rybka, Vlastik; Rybková, Romana; Lưu, Hồng Trường; Nuraliev, Maxim; Leong-Škorničková, Jana (Phytotaxa, 2019)
Two new ginger species, Meistera caudata and Meistera sudae (Zingiberaceae: Alpinieae) from Bidoup-Núi Bà National Park in southern Vietnam, are presented here. Descriptions, notes on distribution, ecology and phenology, preliminary IUCN assessments and colour plates are provided for each newly described species. A new combination Meistera cristatissima, based on Amomum cristatissimum, is also proposed. A previously proposed IUCN preliminary assessment is amended using information from additional collections, and the new extent of known distribution of the species is discussed.